Production method of straw carbon-based plate
By mixing straw fibers with gypsum powder and paving, hot pressing and oxygen-free calcining, the problems of environmental pollution and operation hazards in the preparation of straw carbon-based materials in the prior art were solved, and straw carbon-based plates with porous structures were prepared, which broadened its application scope and achieved efficient adsorption and purification of gases and water bodies.
Patent Information
- Application Number
- CN202411605101.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-03-25
AI Technical Summary
The prior art has problems such as environmental pollution, operating hazards, inconvenient material form and single pore size leading to single adsorption function when preparing straw carbon-based materials.
The method of mixing straw fibers with gypsum powder for paving, hot pressing and oxygen-free calcining is adopted to avoid alkali treatment and pre-activated treatment, and a straw carbon substrate with micropores, mesopories and macropores are formed.
The preparation of straw carbon substrates with environmentally friendly, safe, convenient form and porous structure has been achieved, and its scope of application is expanded, and it is suitable for adsorption, purification and filtration of gases and water bodies.
Smart Images

Figure CN119684021A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of biomass pyrolysis carbon materials, and in particular to a method for producing a straw carbon-based board. Background Art
[0002] Activated carbon has a developed pore structure, high specific surface area and surface activity, and diverse surface chemical properties. It is a widely used high-efficiency adsorbent. Coal, wood, fruit shells, etc. can all be raw materials for making activated carbon. Under the premise of increasing resource shortage and the demand for high value-added utilization of straw materials, there are records in the prior art of using straw as raw material to make straw carbon-based materials by means of biomass pyrolysis.
[0003] Physical activation method generally uses water vapor, carbon dioxide, air or their mixed gases as activators to calcine the straw materials at 750-1100℃ to obtain activated carbon. Chemical activation method generally uses strong acid, strong alkali or salt as activators to impregnate the raw materials in a certain proportion, react at 500-900℃, and obtain activated carbon after washing the reaction products.
[0004] For example, a method for preparing porous carbon from corn straw is disclosed in a Chinese invention patent application with application number CN118546556A and titled “A porous carbon@polyaniline composite material, its preparation method and application, corn straw carbon-based coating and coating”: (1) corn straw powder is mixed with an alkaline solution and subjected to alkaline treatment to obtain alkaline-treated corn straw powder; (2) the alkaline-treated corn straw powder is mixed with a bicarbonate solution and pre-activated to obtain pre-activated corn straw powder, wherein the pre-activation temperature is 80°C and the pre-activation time is 8 to 12 hours; (3) under the protection of an inert gas, the pre-activated corn straw powder is calcined to obtain porous corn straw carbon, wherein the calcination temperature is 400 to 750°C and the insulation time is 1 to 3 hours. The specific surface area of the prepared porous corn straw carbon is 229.7 m 2 / g, the porosity is 0.402 and the average pore size is 0.427nm. Summary of the invention
[0005] The inventors believe that the technical solutions of the prior art still have the following problems: (1) the straw fibers need to be subjected to alkali treatment and pre-activation treatment, which causes environmental pollution and relatively dangerous operation; (2) the straw carbon-based material obtained by calcination is in the form of particles, which is inconvenient to use and has a narrow range of uses; (3) the pore size is single, and generally, its surface pores are composed of mesopores, so the adsorption function is relatively single.
[0006] In order to overcome the pollution problems and narrow applications of straw carbon-based boards in the prior art, the present application provides a method for producing straw carbon-based boards. The method of the present application does not use alkali treatment and pre-activation treatment, and is relatively safe and environmentally friendly. The method of the present application can prepare straw carbon-based boards, which are relatively convenient to use and can be directly used as an adsorption plate. In particular, the method of the present application can prepare straw carbon-based boards whose surface pores include micropores, mesopores and macropores, so they have a relatively wide range of applications and can be used for the adsorption and purification of gases and water bodies. The present application specifically adopts the following technical solutions: A method for producing a straw carbon-based board comprises the following steps: mixing straw fiber and gypsum powder and then paving the mixed material, hot pressing the paved blank at a temperature of 160-240° C. and a pressure of 1-1.2 MPa, and finally anaerobic calcining the blank obtained by the hot pressing at a temperature of 450-800° C. and a time of 1-3 hours, thereby obtaining the straw carbon-based board.
[0007] By the above method, straw fiber is mixed with gypsum powder, and the straw carbon-based board is obtained by paving, hot pressing and calcining. Each process of the method of the present application is a physical treatment using temperature and pressure, so it can effectively avoid environmental pollution and reduce the risk in production. In addition, the production cycle of the straw carbon-based board can be shortened.
[0008] The principle of the method of the present application for preparing a straw carbon-based board with a porous structure is that the original lignin in the straw and the lignin formed by the degradation of hemicellulose are in a molten state at the same time, and the molten lignin acts as a binder to connect the straw fibers with the straw fibers, and the straw fibers with the gypsum powder. The water vapor (mainly including the water vapor generated by the carbonization of the straw and the water vapor generated by the dehydration process of the gypsum) formed by the straw fibers and the gypsum powder at high temperature cannot be discharged in time and forms pores in the connected straw and gypsum, so that the blank can be pressed into a slab with a certain strength, stable shape and a certain number of mesopores inside. Subsequently, through the above-mentioned anaerobic calcination process conditions, under the bonding effect of lignin, the water vapor generated by the decomposition of the gypsum cannot escape in time and leaves pores inside the primary particles. At the same time, the anhydrous gypsum particles generated by the decomposition of the gypsum form additional physical spaces in the straw carbonized material to form pores.
[0009] In the above principle, mesopores can be formed by the straw material itself during the carbonization process, macropores can be formed by the space left by the evaporation of water during the dehydration of gypsum, macropores can be left inside due to the inability of the gas (mainly water vapor) produced by the decomposition of gypsum under the bonding action of lignin to escape in time, and micropores can be formed by the additional physical space formed by the anhydrous gypsum particles produced by the decomposition of gypsum in the straw carbonized material.
[0010] Therefore, the surface of the prepared straw carbon-based board has micropores, mesopores and macropores formed by hot pressing and oxygen-free calcination, which makes it have better porosity, adsorption performance and permeability, and can be used for the adsorption, purification and filtration of gas and water. At the same time, by adding gypsum powder and coordinating the oxygen-free calcination process, the mechanical strength of the straw carbon-based board can be more effectively increased, making it not easy to break, and can be directly used as an adsorption board.
[0011] Preferably, the moisture content of the straw fiber is 5-7%, and the gypsum powder is dihydrate gypsum.
[0012] As a further preference, the length of the straw fiber is 8-12 mm.
[0013] Preferably, in the blank, the added mass ratio of the straw fiber to the gypsum powder is 1:(0.2~0.3).
[0014] Preferably, the density of the slab obtained by hot pressing is 1.2-1.5 g / cm 3 .
[0015] As a further preference, the hot pressing process is a two-stage hot pressing process, wherein the temperature of the first stage of hot pressing is 230-240°C and the pressure is 1-1.2 MPa, and the temperature of the second stage of hot pressing is 160-180°C and the pressure is 1-1.2 MPa.
[0016] As a further preference, the blank is cooled to 130-140° C. between the first stage hot pressing and the second stage hot pressing.
[0017] Preferably, the straw fiber, the gypsum powder and the industrial lignin powder are mixed and then paved to obtain the blank, and the mass ratio of the straw fiber, the gypsum powder and the industrial lignin powder is 1:(0.2~0.3):(0.01~0.02).
[0018] Preferably, the process of oxygen-free calcination is a three-stage oxygen-free calcination process, wherein the temperature of the first stage is 450-500°C, the temperature of the second stage is 600-650°C, and the temperature of the third stage is 750-800°C.
[0019] As a further preference, during the oxygen-free calcination process, the heating rate of the first stage is 175-200°C / h, and the heating rate of the third stage is 125-150°C.
[0020] The straw carbon-based board material prepared by the method of the present application comprises mixed carbonized straw fibers, hemihydrate gypsum and / or anhydrous gypsum, and the surface of the modified straw carbon-based board material comprises micropores, mesopores and macropores, the pore size of the micropores is 1.5~1.9nm, the pore size of the mesopores is 3.1~3.7nm, and the pore size of the macropores is 50~70nm; the ratio of the specific surface area of the mesopores to the micropores is 1:(10~15).
[0021] Preferably, the straw carbon-based board has a thickness of 1 to 20 mm.
[0022] The present application also provides a filter plate for an air purifier, wherein the filter plate comprises a frame and a plurality of straw carbon-based plates installed through the frame, and the thickness of the straw carbon-based plates is 1 to 5 mm.
[0023] The present application also provides a wall adsorption plate, which includes a frame and a plurality of straw carbon-based plates installed through the frame, and the thickness of the straw carbon-based plates is 5~12mm.
[0024] The present application also provides a water filter plate, which includes the straw carbon-based plate and a glass fiber woven bag sleeved outside the straw carbon-based plate, and the thickness of the straw carbon-based plate is 10~20mm.
[0025] In summary, the present application provides a method for producing a straw carbon-based board, which does not use alkali treatment and pre-activation treatment and is relatively safe and environmentally friendly.
[0026] The straw carbon-based board material prepared by the method of the present application can be directly used as an adsorption board, for example, as a wall decoration board, one of the material layers of the filter board of an air purifier, or a partition in furniture that does not support weight, etc., which broadens the application scenarios of the straw carbon-based board material.
[0027] The straw carbon-based board material that can be prepared using the method of the present application has surface pores including micropores, mesopores and macropores, so it has a relatively wide range of applications. Combined with its plate-like structure, it can be used for the adsorption, purification and filtration of gases and water bodies. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without paying any creative labor.
[0029] Figure 1 This is a photo of the straw carbon-based board material of Example 1 of the present application. DETAILED DESCRIPTION
[0030] In order to enable those skilled in the art to better understand the technical solutions in the present application, the technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of this application. Example
[0031] Experimental materials: corn straw fiber, with a moisture content of 5-7% and a length of 8-12 mm, purchased from the market; gypsum powder, dihydrate gypsum (CaSO4·2H2O) powder with a moisture content of less than 1%, with a particle size of 200-300 mesh, purchased from the market.
[0032] Step 1: Mix straw fiber and gypsum powder in a ratio of 10:2 to obtain mixed powder.
[0033] Step 2: Spread the mixed powder in a mold to obtain a blank with a specification of 50 mm×50 mm×2.5 mm.
[0034] Step three, hot pressing the blank. The hot pressing process is a two-stage process, in which the temperature of the first stage is 240°C, the pressure is 1MPa, and the time is 3min; then, the temperature of the upper and lower pressing plates is lowered to reduce the temperature of the blank to between 130 and 140°C, but the pressure should not be removed or reduced during the cooling process; finally, the temperature of the upper and lower pressing plates is increased to allow the blank to enter the second stage of hot pressing, and the temperature of the second stage of hot pressing is 160°C, the pressure is 1MPa, and the time is 5min. The thickness of the slab obtained in this step is 2mm, and the density is 1.2~1.5g / cm 3 The cooling treatment between the first and second stages of hot pressing can help fix the shape of the blank and improve the bonding strength.
[0035] Step 4: calcining the slab in an oxygen-free environment under nitrogen protection. The oxygen-free calcination process is a three-stage process, with a temperature of 450°C, a heating rate of 175-200°C / h, and calcination for 1 hour in the first stage, a temperature of 700°C, and calcination for 1 hour in the second stage, and a temperature of 750°C, a heating rate of 125-150°C, and calcination for 1 hour in the third stage.
[0036] A straw carbon-based board with a specification of 50mm×50mm×2mm was prepared, with a porosity of 61%, a macropore diameter of 50-70nm, an average mesopore diameter of 3.26nm, an average micropore diameter of 1.60nm, a specific surface area ratio of mesopores to micropores of 1:14, a wear resistance of not less than 97%, a crushing strength of not less than 6.3MPa, and a toluene adsorption rate of 19.2%.
[0037] Among them, the reason why the porosity of the straw carbon-based board material in this embodiment is relatively high is that mesopores and micropores can be formed on the pore walls of the macropores, so that the macropores have both permeability and adsorption.
[0038] Take four pieces of the straw carbon-based board material, and by splicing, bonding and embedding them into a frame, they can be made into filter plates for air purifiers. Example
[0039] The difference between this embodiment and embodiment 1 is that the ratio of straw fiber to gypsum powder is 10:3. The prepared straw carbon-based plate has a porosity of 59%, a macropore diameter of 50-70 nm, an average mesopore diameter of 3.31 nm, an average micropore diameter of 1.72 nm, a ratio of mesopore to micropore specific surface area of 1:12, a wear resistance of not less than 96%, a crushing strength of not less than 5.9 MPa, and a toluene adsorption rate of 18.6%. Example
[0040] Experimental materials: corn straw fiber, with a moisture content of 5-7% and a length of 8-12 mm, purchased from the market; gypsum powder, dihydrate gypsum (CaSO4·2H2O) powder with a moisture content of less than 1%, with a particle size of 200-300 mesh, purchased from the market.
[0041] Step 1: Mix straw fiber, gypsum powder and industrial lignin in a ratio of 10:2:0.1 to obtain a mixed powder.
[0042] Step 2: Spread the mixed powder in a mold to obtain a blank with a specification of 50 mm×50 mm×8.5 mm.
[0043] Step three, hot pressing the blank. The hot pressing process is a two-stage process, in which the temperature of the first stage is 240°C, the pressure is 1.2MPa, and the time is 4min; then, the temperature of the upper and lower pressing plates is lowered to reduce the temperature of the blank to between 130 and 140°C, but the pressure should not be removed or reduced during the cooling process; finally, the temperature of the upper and lower pressing plates is increased to allow the blank to enter the second stage of hot pressing, and the temperature of the second stage of hot pressing is 180°C, the pressure is 1.2MPa, and the time is 5min. The thickness of the slab obtained in this step is 7mm, and the density is 1.2~1.5g / cm 3 .
[0044] Step 4: calcining the slab in an oxygen-free environment under nitrogen protection. The oxygen-free calcining process is a three-stage process, with a temperature of 500°C, a heating rate of 175-200°C / h, and calcination for 1 hour in the first stage, a temperature of 650°C, and calcination for 1 hour in the second stage, and a temperature of 800°C, a heating rate of 125-150°C, and calcination for 1 hour in the third stage.
[0045] A straw carbon-based board with a specification of 50mm×50mm×7mm was prepared, with a porosity of 53%, a macropore diameter of 50~70nm, an average mesopore diameter of 3.47nm, an average micropore diameter of 1.79nm, a specific surface area ratio of mesopores to micropores of 1:10, a wear resistance of not less than 95%, a crushing strength of not less than 6.8MPa, and a toluene adsorption rate of 17.3%.
[0046] Take a number of the above straw carbon-based boards and composite them into a 1mm thick and 1.0g / cm density board by splicing and bonding. 3 The surface of the high-density fiberboard can be used as a wall adsorption board. Example
[0047] The difference between this embodiment and embodiment 3 is that, in step one, the ratio of straw fiber, gypsum powder and industrial lignin is 10:2:0.2; in step two, the specification of the blank obtained by paving is 50mm×50mm×14.5mm; in step three, the thickness of the slab obtained by hot pressing is 12mm; in step four, a straw carbon-based plate with a specification of 50mm×50mm×12mm is obtained by calcination, the porosity of which is 51%, the macropore diameter is 50~70nm, the average mesopore diameter is 3.68nm, the average micropore diameter is 1.85nm, the specific surface area ratio of mesopores to micropores is 1:10, the wear resistance is not less than 95%, the crushing strength is not less than 7.3MPa, and the toluene adsorption rate is 17.6%.
[0048] Take a number of the above-mentioned straw carbon-based sheets, put them into a glass fiber woven bag to form a rectangular sheet structure, and put them into a fish tank with goldfish to serve as a water filter plate. The COD removal rate (Chemical Oxygen Demand) is not less than 99%, the BOD removal rate (Biochemical oxygen demand) is not less than 99%, and the phosphate removal rate is not less than 92%. In addition, as a self-adhesive sheet, the water filter plate prepared from the straw carbon-based sheet of this embodiment also has an indicator effect. In other words, when the straw carbon-based sheet loses the shape of the sheet and becomes carbon residue in the glass fiber woven bag, it can be considered that the water filter plate should be replaced.
[0049] The COD removal rate (chemical oxygen demand) of the water filter plate of the existing technology is not less than 97%, the BOD removal rate (biochemical oxygen demand) is not less than 98%, and the phosphate removal rate is not less than 91%, but it does not have an indicating effect.
[0050] The above description is intended to be illustrative and not limiting. Upon reading the above description, many embodiments and many applications beyond the examples provided will be apparent to those skilled in the art. Therefore, the scope of the present teachings should not be determined with reference to the above description, but should be determined with reference to the appended claims and the full scope of equivalents to which such claims are entitled. For the purpose of comprehensiveness, all articles and references, including disclosures of patent applications and publications, are incorporated herein by reference. The omission of any aspect of the subject matter disclosed herein in the preceding claims is not intended to be a waiver of the subject matter, nor should it be considered that the applicant has not considered the subject matter to be part of the disclosed application subject matter.
Claims
1. A method for producing a straw carbon-based board, characterized in that: The straw fiber is mixed with gypsum powder and then paved. The paved blank is hot pressed at a temperature of 160-240°C and a pressure of 1-1.2 MPa. Finally, the slab obtained by hot pressing is anaerobic calcined at a temperature of 450-800°C and a time of 1-3 hours, thereby obtaining the straw carbon-based board.
2. The method for producing a straw carbon-based board according to claim 1, characterized in that: The moisture content of the straw fiber is 5-7%, and the gypsum powder is dihydrate gypsum.
3. The method for producing a straw carbon-based board according to claim 1 or 2, characterized in that: The length of the straw fiber is 8-12 mm.
4. The method for producing the straw carbon-based board according to claim 1, characterized in that: In the blank, the added mass ratio of the straw fiber to the gypsum powder is 1:(0.2-0.3).
5. The method for producing the straw carbon-based board according to claim 1, characterized in that: The density of the slab obtained by hot pressing is 1.2-1.5 g / cm 3 .
6. The method for producing the straw carbon-based board according to claim 5, characterized in that: The hot pressing process is a two-stage hot pressing process, the temperature of the first stage hot pressing is 230~240℃ and the pressure is 1~1.2MPa, and the temperature of the second stage hot pressing is 160~180℃ and the pressure is 1~1.2MPa.
7. The method for producing a straw carbon-based board according to claim 1, characterized in that: The straw fiber, the gypsum powder and the industrial lignin powder are mixed and then paved to obtain the blank, and the mass ratio of the straw fiber, the gypsum powder and the industrial lignin powder is 1:(0.2~0.3):(0.01~0.02).
8. The method for producing the straw carbon-based board according to claim 1, characterized in that: The process of oxygen-free calcination is a three-stage oxygen-free calcination process, with the temperature of the first stage being 450~500℃, the temperature of the second stage being 600~650℃, and the temperature of the third stage being 750~800℃.
9. The method for producing the straw carbon-based board according to claim 8, characterized in that: In step three, the heating rate of the first stage is 175-200°C / h, and the heating rate of the third stage is 125-150°C.
10. The method for producing a straw carbon-based board according to claim 1, characterized in that: The prepared straw carbon-based board material comprises mixed carbonized straw fibers, hemihydrate gypsum and / or anhydrous gypsum, and the surface of the straw carbon-based board material comprises micropores, mesopores and macropores, the pore diameter of the micropores is 1.5-1.9 nm, the pore diameter of the mesopores is 3.1-3.7 nm, and the pore diameter of the macropores is 50-70 nm; the ratio of the specific surface area of the mesopores to the micropores is 1:(10-15).
Citation Information
Patent Citations
Porous carbon coated polyaniline composite material, preparation method and application thereof, corn stalk carbon-based paint and coating
CN118546556A